AB0772 Ocular manifestations of behcet's disease. (23rd January 2014) - Goloeva, R.G.; Alekberova, Z.; Tankovskyi, V.; Guseva, I.
Abstract : Objectives: To study of ocular pathology in BD and association with clinical features, gender and the antigen HLA-B51. Methods: 250 BD pts were evaluated in the Research Institute of Rheumatology RAMS from 1990 to 2010 years. BD was diagnosed according to criteria of International Study Group for Behcet's Disease (ISGBD). The test for HLA B51 was performed using microlymphocytotoxity method. Results: Ocular involvement were revealed in 135 of patients: lesion anterior and posterior segments of the eye (punuveitis) had 53% of pts, of occlusive retinopathy - 29%, isolated retinal vasculitis - 30%, hypopyon - 12%. Manifestation of ocular pathology with of venous thrombosis of the retina was found in 3% of pts. In 8% of the pts eye involvement was the first symptom. The mean age at onset of uveitis was 25 years [21, 30], the eyes were involved in the process of the 3-d year disease [1, 6]. In 15 patients with decreased visual acuity in both eyes is less than 0.1 for the third year course of uveitis, 10 patients lost vision in one eye and a significant decrease in visual acuity second eye (less than 0.1) for 5 years course of uveitis [2, 5, 6]. Three men were blind to the 3-d year of illness. The vast majority of patients with significant loss of visual function has been a late diagnosis and delayed treatment. Uveitis is diagnosed more often in male patients, the male-to-female ratio was 4, 6:1. We found correlation of uveitis with male sex (r=0, 27, p=0, 00001), the antigen HLA-B51 (r=0, 25, p=0, 0003) and a negative correlation with gastrointestinal lesions (r= -0, 16, p=0, 008). Conclusions: Eye involvement in BD associated with male gender and HLA-B51 antigens. Disclosure of Interest: None Declared